2014
DOI: 10.1021/ja5019223
|View full text |Cite
|
Sign up to set email alerts
|

Direct Decarboxylation of 5-Carboxylcytosine by DNA C5- Methyltransferases

Abstract: S-Adenosylmethionine-dependent DNA methyltransferases (MTases) perform direct methylation of cytosine to yield 5-methylcytosine (5mC), which serves as part of the epigenetic regulation mechanism in vertebrates. Active demethylation of 5mC by TET oxygenases produces 5-formylcytosine (fC) and 5-carboxylcytosine (caC), which were shown to be enzymatically excised and then replaced with an unmodified nucleotide. Here we find that both bacterial and mammalian C5-MTases can catalyze the direct decarboxylation of caC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 29 publications
0
44
0
4
Order By: Relevance
“…5 However, supraphysiological concentrations of Ca 2C are required for this reaction to occur (1 mM Ca 2C is optimal for demethylation; the minimum concentration is 10 mM). Apart from a direct action on 5mC and 5hmC, again in the absence of SAM, DNMT-3A and -3B can also directly convert 5caC, but not 5fC, into unmodified C. 36 These results indicate the intriguing possibility that active DNA demethylation can proceed via the reduction of oxidized products of 5mC without the need for BER, although these processes may serve as complementary pathways to BER.…”
mentioning
confidence: 94%
“…5 However, supraphysiological concentrations of Ca 2C are required for this reaction to occur (1 mM Ca 2C is optimal for demethylation; the minimum concentration is 10 mM). Apart from a direct action on 5mC and 5hmC, again in the absence of SAM, DNMT-3A and -3B can also directly convert 5caC, but not 5fC, into unmodified C. 36 These results indicate the intriguing possibility that active DNA demethylation can proceed via the reduction of oxidized products of 5mC without the need for BER, although these processes may serve as complementary pathways to BER.…”
mentioning
confidence: 94%
“…162 One study finds that DNA methyltransferases, including the human Dnmt3A/B Dnmt3L complex, converts 5caC to C in vitro , but the activity was reduced in the presence of physiological levels of S -adenosylmethionine (SAM), a cofactor for DNA methyltransferases, so the biological relevance remains to be established. 164 Studies of non-enzymatic decarboxylation of 5caC (in DNA) revealed an efficient thiol-mediated, acid catalyzed reaction. 165 The proposed mechanism involves attack at the C6 position of 5caC by a Cys side chain, giving an activated intermediate with a saturated C5-C6 bond that leads to decarboxylation, thiol expulsion, and re-aromatization (Figure 12).…”
Section: Ber Mediates Active Dna Demethylation Vertebratesmentioning
confidence: 99%
“…These suggest that normal development requires the proper activities of DNMT3 enzymes. Although DNMTs are known to methylate DNA, it is interesting that DNMT1 and DNMT3A/B have been also shown to regulate the removal of methylation by decarboxylation (Liutkeviciute et al, 2014) or by yielding 5-hydroxymethylcytosine (Liutkeviciute et al, 2011). Although there is currently more understanding for the roles of DNMT1 and DNMT3 enzymes, the roles of DNMT2 enzymes have been under debate.…”
Section: Dna Methylation Machinerymentioning
confidence: 99%
“…This model suggests that demethylation occurs either by: (i) deamination of 5hmC to 5hmU by AID/APOBECs (a family of cytidine deaminases) (AIDActivation Induced Deaminase) followed by the excision of 5hmU by glycosylases (such as TDG, Thymine DNA Glycosylase) and replacement with cytosine through the BER pathway (Cortazar et al, 2011;Cortellino et al, 2011;Guo et al, 2011): or (ii) oxidation of 5hmC to 5fC and 5caC followed by replacement as described for 5hmC (above) by the BER pathway Ito et al, 2011;Maiti and Drohat, 2011). Other possible mechanisms may include conversion of 5fC or 5caC to cytosine catalysed by a decarboxylase enzyme (Ito et al, 2011;Liutkeviciute et al, 2014). Recent discoveries suggest that TETmediated derivatives of 5meC (5hmC, 5fC, 5caC) can be the intermediates in active demethylation pathway which is the most widely accepted hypothesis of global demethylation (Tahiliani et al, 2009;Guo et al, 2011) and reported with the loss of 5meC from the paternally-inherited genome (compared to that inherited from the oocyte) immediately following fertilisation (McLay and Clarke, 2003;Iqbal et al, 2011;Silva et al, 2011).…”
Section: Bisulfite Sequencingmentioning
confidence: 99%